2023
DOI: 10.21037/jtd-23-1086
|View full text |Cite
|
Sign up to set email alerts
|

Selection of key genes for dilated cardiomyopathy based on machine learning algorithms and assessment of diagnostic accuracy

Tingting Chen,
Xiulin Xuan,
Jiajia Ni
et al.

Abstract: Background The mechanisms of the occurrence and progression of dilated cardiomyopathy are still unclear and further exploration is needed. The upgrading of programming languages and the improvement of biological databases have created conditions for us to explore the structural and functional information of biological molecules at the nucleic acid and protein levels, screen key pathogenic genes, and elucidate pathogenic mechanisms. This study aimed to screen key pathogenic genes using machine lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Echocardiographic review with a minimum interval of 12 months from baseline excluded changes in LVEF due to short-term changes in heart rate or hemodynamic load in favor of the prognosis gap due to intrinsic pathogenesis. Differential analysis of cardiomyopathy microarray data from Gene Expression Omnibus (GEO) has been previously conducted, and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment has revealed that differentially expressed genes are significantly enriched in cytokine-cytokine receptor interactions, natural killer cell-mediated cytotoxicity ( 16 , 17 ), cell adhesion molecules, and Th17 cell differentiation signaling pathways. Viral infection may cause the above-mentioned immune response and affect the prognosis of children.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic review with a minimum interval of 12 months from baseline excluded changes in LVEF due to short-term changes in heart rate or hemodynamic load in favor of the prognosis gap due to intrinsic pathogenesis. Differential analysis of cardiomyopathy microarray data from Gene Expression Omnibus (GEO) has been previously conducted, and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment has revealed that differentially expressed genes are significantly enriched in cytokine-cytokine receptor interactions, natural killer cell-mediated cytotoxicity ( 16 , 17 ), cell adhesion molecules, and Th17 cell differentiation signaling pathways. Viral infection may cause the above-mentioned immune response and affect the prognosis of children.…”
Section: Discussionmentioning
confidence: 99%